2006
DOI: 10.1002/ajh.20582
|View full text |Cite
|
Sign up to set email alerts
|

Distinct association of factor V-Leiden and prothrombin G20210A mutations with deep venous thrombosis in Tunisia and Lebanon

Abstract: Factor V G1691A (FV‐Leiden) and prothrombin (PRT) G20210A single nucleotide polymorphisms (SNPs) were associated with venous thrombosis among Caucasians. We assessed the contribution of both SNPs to the genetic susceptibility of deep venous thrombosis (DVT) among Lebanese and Tunisian patients. Subjects comprised 198 DVT patients and 540 healthy controls from Lebanon and 126 Tunisian DVT patients and 197 control subjects; FV‐Leiden (MnlI) and PRT G20210A (HindIII) genotyping was done by PCR‐RFLP. While the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…We note also that the prevalence of the FVL mutation in our population is different from other Tunisian studies in the centre of Tunisia [18][19][20]. Ajem et al reported a prevalence of 6% in a healthy population of 100 cases [19].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…We note also that the prevalence of the FVL mutation in our population is different from other Tunisian studies in the centre of Tunisia [18][19][20]. Ajem et al reported a prevalence of 6% in a healthy population of 100 cases [19].…”
Section: Discussioncontrasting
confidence: 92%
“…Ajem et al reported a prevalence of 6% in a healthy population of 100 cases [19]. Others found a frequency of 6.4% in 313 studied subjects [20] and 6.1% in 197 cases [18]. This could be attributed to differences in sample size and geographic origin of the studied subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Factor V Leiden is not observed in Asian or African native populations [1][2][3][4][5][6], whereas it is present with high variability depending on the origin of the population in regions with historical mixing of different ethnic origin population such as in Middle Eastern [7][8][9]. In Europe, a high prevalence is observed with differences between European countries.…”
Section: Introductionmentioning
confidence: 96%
“…Alone, this mutation results in a 3-to 7-fold greater risk of VTE development (Nizankowska-Mogilnicka et al, 2003;Bouaziz-Borgi et al, 2006). When associated with the FV G1691A allele, the risk and recurrence of thrombotic disease increases significantly (Ehrenforth et al, 2004;Marchiori et al, 2007).…”
Section: Introductionmentioning
confidence: 99%